Critical Learning Ethics in the Qur’an: Insights from Qur'an 17:36 (Al-Isra: 36) for Digital Literacy - Muhammad Burhan Ashfiya’; Syarief Fathimatuz Zahro; Akbar Arrafi Yuswono; Ahmad Yusam Thobroni (AL GHAZALI: Jurnal Pendidikan dan Pemikiran Islam, 2026)
This study aims to analyze the ethics of critical learning in the Qur’an through a tarbawi interpretation approach of QS. Al-Isra: 36 in the context of digital literacy. The main problem of this study is the low level of critical thinking ability in digital learning practices that is not balanced with adequate ethical foundations. The research employs a descriptive qualitative approach based on library research using a thematic interpretation (maudhu’i) method that integrates textual analysis of the verse with the context of contemporary education. Data are analyzed through stages of identifying the meaning of the verse, linguistic analysis, and synthesizing educational values contextualized with digital literacy using qualitative content analysis. The results show that QS. Al-Isra: 36 contains principles of critical learning ethics, including information verification, rational thinking, rejection of following without knowledge-based evidence, and intellectual responsibility. The findings also indicate a gap between the normative values of learning ethics in Islam and digital learning practices that tend to be instant and non-reflective. This study emphasizes that tarbawi interpretation can function as a bridge between Qur’anic values and the needs of modern digital literacy. The theoretical contribution of this study lies in strengthening the concept of learning ethics as an integration of cognitive and moral dimensions, while its practical contribution is the development of applicable indicators of critical learning ethics in digital learning. This study recommends the integration of Qur’anic values into the curriculum to strengthen ethical digital literacy and to foster learners who are critical and responsible.